Characterization of Monocyte‐Derived Dendritic Cells from Immunosuppressed Renal Transplant Recipients with and without Squamous Cell Carcinomas. (22nd August 2013) - Sandvik, L. F.; Volchenkov, R.; Jonsson, R.; Appel, S.
Abstract: Renal transplant recipients (RTR) have a high risk of tumour development, especially cutaneous squamous cell carcinomas (SCC), due to long‐term immunosuppressive therapy. RTR may develop multiple lesions over short time periods, and these are often more aggressive with a higher risk of local recurrence and metastasis resulting in increased morbidity and mortality in these patients. Therefore, we took the first step towards evaluating the possibility of generating a therapeutic vaccine based on monocyte‐derived dendritic cells (moDC) for these patients. We analysed the phenotype and cytokine/chemokine profile of moDC from long‐term immunosuppressed RTR with and without previous SCC. The number of peripheral blood mononuclear cells (PBMC) isolated per ml blood as well as the efficiency of generating moDC from peripheral blood mononuclear cells (PBMC) was similar in patients and immunocompetent controls. Phenotype and cytokine/chemokine profile of the moDC from immunosuppressed patients were similar to those from immunocompetent controls, making moDC‐based immunotherapy a potential future treatment option for RTR with multiple SCC.